Posterior Fossa Tumors - Drevelegas, Antonios; Chourmouzi, Danai; Constantinides, Manos; Drevelegas, Konstantinos (Journal of Pediatric Neuroradiology, 2016)
In this article, we review the most common posterior fossa pediatric neoplasms. We describe the computed tomography and magnetic resonance imaging (MRI) findings used in the initial evaluation of a pediatric brain tumors. We also discuss the advanced MRI techniques which provide information about the physiology of the tumors and play an important role in the differential diagnosis as well as in the preoperative evaluation of different tumor types.
Keywords: pediatric posterior fossa tumor; pilocytic astrocytoma; medulloblastoma; ependymomas; brain stem glioma; magnetic resonance imaging